Engineered multitargeting exosomes carrying miR-323a-3p for CRC therapy - Pang, Yechun; Chen, Xingshi; Xu, Baiying; Zhang, Yuanzhou; Liang, Shunshun; Hu, Jingying; Liu, Rui; Luo, Xiaoying; Wang, Yunfeng (International journal of biological macromolecules, 2023)
Colorectal cancer (CRC) is in the forefront of malignancies for its high incidence and mortality. 5-Fluorouracil (5-FU) is one of the most widely used effective drugs for the treatment of CRC. However, there is an urgent need in reducing its systemic side effects and chemoresistance, in order to make 5-FU-based chemotherapy more effective in the treatment of CRC. In this study, engineered CRC cells were established to overexpress miR-323a-3p, which was a tumor suppressor that targeted both EGFR and TYMS. Then miR-323a-3p-loaded exosomes (miR-Exo) were obtained with suitable methods of collection and purification. We found that miR-Exo significantly inhibited CRC cell proliferation and induced apoptosis by the way of targeting EGFR directly in the cells, which eventually led to desirable tumor regression in the cell derived xenograft (CDX) and patient derived xenograft (PDX) tumor mice models. Moreover, we discovered that miR-323a-3p released from miR-Exo directly inhibited the upregulation of thymidylate synthase (TYMS) induced by 5-FU-resistence in CRC cells, resulting in the revival of tumor cytotoxicity from 5-FU. MiR-Exo could effectively induce the CRC cell apoptosis by targeting EGFR and TYMS, and enhance the therapeutic effects of 5-FU on CRC. Our work demonstrates the potency of miR-Exo for advanced CRC biotherapy.